Physical simulation of GaN based HEMT - Vais, Abhitosh (My University, 2012)
Recent improvements in the understanding and fabrication of GaN have led to its application in high frequency communication and high voltage switching systems. Requirement for operation at even higher frequency and voltages is driving the research currently on design of GaN based devices which can operate at frequencies above 30 GHz and voltages up to 100 V. Reliability issues with GaN based devices operating in such conditions and lack of understanding of various phenomena are some of the factors hindering their widespread commercial development. There is a need to understand the device operation by developing a simulation model, as close to reality as possible, which could be, further, used to optimize the device design for high frequency and power operation. Recent improvements in the understanding and fabrication of GaN have led to its application in high frequency communication and high voltage switching systems. Requirement for operation at even higher frequency and voltages is driving the research currently on design of GaN based devices which can operate at frequencies above 30 GHz and voltages up to 100 V. Reliability issues with GaN based devices operating in such conditions and lack of understanding of various phenomena are some of the factors hindering their widespread commercial development. There is a need to understand the device operation by developing a simulation model, as close to reality as possible, which could be, further, used to optimize the device design for high frequency and power operation. This thesis work reports the design and development of a physical simulation model of AlGaN/GaN High Electron Mobility Transistor (HEMT) using commercial software (Synopsys, Sentaurus TCAD). The model is calibrated against measurement data. The results show a close matching with measured data, although some discrepancies have been found in the linear region of DC operation and high frequency regime of AC analysis. It is observed that trap density and their energy level (surface and bulk) play an important role in device characteristics. Effects of including quantum calculations in the model are analyzed. Various methods to improve the operating frequency have been investigated. The results show that by tuning the drain to gate distance, gate length and AlGaN thickness, AC characteristics can be improved significantly (fmax > 150 GHz). The influence of changing the epitaxial layer structure (adding more layers) on the device's AC characteristics is analysed to find an optimum design for high frequency applications.
Keywords: Elektroteknik och elektronik; Elektronik; Informations- och kommunikationsteknik; Electrical Engineering, Electronic Engineering, Information Engineering; Electronics; Information & Communication Technology